2018
DOI: 10.1007/978-3-319-95174-4_39
|View full text |Cite
|
Sign up to set email alerts
|

Study of Various Classifiers for Identification and Classification of Non-functional Requirements

Abstract: Identification of non-functional requirements in an early phase of software development process is crucial for creating a proper software design. These requirements are often neglected or given in too general forms. However, interviews and other sources of requirements often include important references also to non-functional requirements which are embedded in a bigger textual context. The non-functional requirements have to be extracted from these contexts and should be presented in a formulated and standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Our work is focusing on comparison the methods including the application of the simplest deep neural network. In our former work, we have compared methods implemented in scikit-learn library [30] using the NFR dataset [38]. Our work has confirmed that the Multinomial Naive Bayes and the SVM might be the best choice if there are only a few labeled examples available.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our work is focusing on comparison the methods including the application of the simplest deep neural network. In our former work, we have compared methods implemented in scikit-learn library [30] using the NFR dataset [38]. Our work has confirmed that the Multinomial Naive Bayes and the SVM might be the best choice if there are only a few labeled examples available.…”
Section: Introductionmentioning
confidence: 71%
“…This assumption has also been confirmed by Groen et al in their investigation [19]. To support System Analysts in choosing the appropriate procedure, investigations have been proceeded for comparison of the performance of the methods [1,9,25,38]. The researchers found that Multinomial Naive Bayes and the Support Vector Machine (SVM) using the linear kernel had given the best performance using only a few labeled examples such as the NFR dataset.…”
Section: Introductionmentioning
confidence: 73%
“…A score of "0.5" means the design or validation is briefly described but lacking relevant details. A score of "0" means there is no description or it is described in such a way that it is not possible to understand the details 2014 CCHIT, WorldVista Automatic analysis [91] 2014 DePaul07 Automatic analysis [94] 2016 DePaul07, Concordia corpus Automatic analysis [74] 2016 Proprietary Automatic analysis [66] 2017 DePaul07 Automatic analysis [72] 2017 Mobile app store reviews Automatic analysis [70] 2017 PTC, MIP, CCHIT Automatic analysis [6] 2018 DePaul07 Automatic analysis [100] 2018 DePaul07 Automatic analysis [42] 2018 TAS, deletaIoT Runtime analysis [60] 2019 Mobile app store reviews Automatic analysis [10] 2019 DePaul07, Predictor models Automatic analysis [106] 2019 DePaul07, CCHIT Automatic analysis in the community. ( 2) Scale and context are key factors for applied fields such as requirements engineering, making it more challenging to design relevant experiments.…”
Section: Validationsmentioning
confidence: 99%
“…There are multiple automated techniques for recognition of structure for a formal document in PDF or other formats. These techniques can be divided into two categories; machine learning techniques [13], [14] and the others are heuristics techniques [15], [16]. These methods use different ways to recognize the structure e.g.…”
Section: B Annotation Of Pdf Artifacts 1) Text Extraction From Pdf Dmentioning
confidence: 99%
“…Ameller [9], Riaz et al [1], Alkussayer et al [10], Vlas and Robinson [11], and Lee [12] used multiple techniques for NFR extractions from the text. These techniques can be categorized into two types (i) Ontological extractions [13]- [16] (ii) Text classifications or tagging [17]. We used text classification scheme for NFR extractions, different machine learning classifiers are analyzed.…”
Section: Introductionmentioning
confidence: 99%